Segmental duplications drive the evolution of accessory regions in a major crop pathogen - van Westerhoven, A.C.; Aguilera-Galvez, C.; Nakasato-Tagami, G.; Shi-Kunne, X.; de la Parte, E.M.; Chavarro-Carrero, E.; Meijer, H.J.G.; Feurtey, A.; Maryani, N.; Ordonez, N.; Schneiders, H.; Nijbroek, K.; et al. (Wiley, 2024)
Many pathogens evolved compartmentalized genomes with conserved core and variable accessory regions (ARs) that carry effector genes mediating virulence. The fungal plant pathogen Fusarium oxysporum has such ARs, often spanning entire chromosomes. The presence of specific ARs influences the host range, and horizontal transfer of ARs can modify the pathogenicity of the receiving strain. However, how these ARs evolve in strains that infect the same host remains largely unknown. We defined the pan-genome of 69 diverse F. oxysporum strains that cause Fusarium wilt of banana, a significant constraint to global banana production, and analyzed the diversity and evolution of the ARs. Accessory regions in F. oxysporum strains infecting the same banana cultivar are highly diverse, and we could not identify any shared genomic regions and in planta-induced effectors. We demonstrate that segmental duplications drive the evolution of ARs. Furthermore, we show that recent segmental duplications specifically in accessory chromosomes cause the expansion of ARs in F. oxysporum. Taken together, we conclude that extensive recent duplications drive the evolution of ARs in F. oxysporum, which contribute to the evolution of virulence.